PAMALI CULTURE AND ISLAMIC EDUCATIONAL LEADERSHIP IN PESANTREN OF SOUTH KALIMANTAN - Wahyudin Wahyudin; Murjani Murjani; Muhammad Zakiyyul Fuad Rasyid (Nurul Jadid University, 2025)
The intersection between local wisdom and Islamic educational leadership provides a significant perspective for understanding leadership practices in pesantren. Pamali culture, as an indigenous cultural value system, offers a unique context for examining how traditional norms influence ethical leadership and educational management. This study examines the role of pamali culture in Islamic educational leadership within pesantren in South Kalimantan. Employing a qualitative ethnographic approach, data were collected through interviews, observations, and documentation involving pesantren leaders, teachers, and students. The findings reveal that pamali culture functions not merely as a cultural heritage of the Banjar community but also as a value system embedded in pesantren life. It contributes to shaping students’ discipline and obedience, strengthening the leadership legitimacy of Tuan Guru, and fostering organizational loyalty and social cohesion within the pesantren community. The study further demonstrates that leadership effectiveness in pesantren is supported not only by formal organizational structures and religious authority but also by local cultural values that are continuously maintained and reproduced within the community.